World Trade Evolution Growth, Productivity and Employment - Ing, Lili Yan; Yu, Miaojie (Routledge-ERIA Studies in Development Economics, 2019)
The book provides theoretical and empirical evidence on how world trade evolves, how trade affects resource allocation, how trade competition affects productivity, how China shock affects world trade and how trade affects large and small countries. It is a useful reference which focuses on new approaches to international trade by looking into country-specific as well as firm-product level-specific cases. "The Open Access version of this book, available at http://www.taylorfrancis.com/books/10.4324/9781351061544, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license."